GENERATION OF ELECTRONS IN AQUEOUS WATER USING THE PRINCIPLE OF INDUCED CURRENT: Received: 25th June 2021; Revised: 7th December 2021, 13th January 2022; Accepted: 17th January 2022 - Low, Kin Onn; Khoo, Kee Tong; Koon, Ying Yao; Chua, Jia Xin (MATTER: International Journal of Science and Technology, 2022)
Drinking water enriched with natural electrons is believed to bring many benefits to people’s health because the electrons are able to destroy free radicals in the human body. This work demonstrated that electrons can be generated when aqueous water is forced to flow through a magnetic field created by a magnetic iron oxide source. The electrons created using this method were shown to affine to positively charged particles, which are the hydrogen ions in the aqueous water. Such affinity created hydrogen-electron pairs and consequently increases the concentration of the hydroxyl ions in the water system when the aqueous water is flown through the magnetic field. When this happened, the pH of the aqueous water increased compared to the aqueous water before flowing through the magnetic field. Similarly, the resistivity of the aqueous water is reduced as a result of the generation of electrons in aqueous water, when the aqueous water flows through the magnetic field.